2009
DOI: 10.1051/0004-6361/200810601
|View full text |Cite
|
Sign up to set email alerts
|

Response of the solar atmosphere to magnetic field evolution in a coronal hole region

Abstract: Context. Coronal holes (CHs) are deemed to be the sources of the fast solar wind streams that lead to recurrent geomagnetic storms and have been intensively investigated, but not all the properties of them are well known. Aims. We study the response of the solar atmosphere to the magnetic field evolution in a CH region, such as magnetic flux emergence and cancellation for both network (NT) and intranetwork (IN) regions. Methods. We study an equatorial CH observed simultaneously by HINODE and STEREO on July 27,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 118 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…Based on Hinode observations, de Wijn et al (2008) found that some of the magnetic elements are associated with the chromospheric cell grains. Recently, although no obvious correlation between the magnetic flux density and the Ca ii H internetwork brightness was obtained, Yang et al (2009) were still inclined to believe that there should be a correlation between the two, and they attributed the lack of correlation to the low cadence of Ca ii H images they used.…”
Section: Nature Of Internetwork Grainsmentioning
confidence: 99%
“…Based on Hinode observations, de Wijn et al (2008) found that some of the magnetic elements are associated with the chromospheric cell grains. Recently, although no obvious correlation between the magnetic flux density and the Ca ii H internetwork brightness was obtained, Yang et al (2009) were still inclined to believe that there should be a correlation between the two, and they attributed the lack of correlation to the low cadence of Ca ii H images they used.…”
Section: Nature Of Internetwork Grainsmentioning
confidence: 99%
“…The EUV Imaging Spectrograph (EIS) can detect changes in outflow velocities expected from the changing loop magnetic topologies (Culhane et al, 2007), and the X-ray Telescope (XRT, Golub et al, 2007) can observe the changes in loop brightness and temperature at CHB reconnection sites. Related Hinode studies of flux emergence and flux cancellation at a CHB (Yang et al, 2009) and of outflows from an active region edge at a CHB (Sakao et al, 2007) did not use the full Hinode instrument suite, which could advance our understanding of the sources of the slow solar wind and of open field transport through CHB studies. …”
Section: Reconnection At Chbsmentioning
confidence: 99%
“…They are known as prominences when they are Figure 1.2: Variation of temperature and density with height from photosphere to corona. Image is taken from Yang et al (2009). seen above the solar limb, as shown in Fig.…”
Section: What Are Prominences?mentioning
confidence: 99%